Faux-Pas Recognition Test: A Turkish Adaptation Study and a Proposal of a Standardized Short Version - ŞANDOR, SERRA; İşcen, Pınar (Routledge Journals, 2021)
Faux Pas Recognition Test (FPRT) is one of the most commonly used tools to assess the theory of mind (ToM) and a valid and reliable screening of this social cognitive function in both clinical and research settings is essential. We aimed to evaluate the psychometric properties of the FPRT on a healthy Turkish sample and to develop a shorter form with adequate psychometric properties to provide an easier application for the tester by shortening the test's duration of administration. Four hundred sixteen healthy individuals completed the Turkish version of the FPRT. Addenbrooke's Cognitive Evaluation-Revised form (ACE-R) was given to the participants who were over 60 years of age in order to eliminate the adverse effects of a potential cognitive decline on FPRT performance. Effects of psychological symptoms on FPRT performance were controlled with Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). Both the original and short versions of the test showed good psychometric properties: for the original version internal consistency reliability was 0.94 for faux-pas (FP) stories and 0.92 for control stories; for the short version it was 0.92 for FP stories and was 0.93 for control stories. For the original version of the FPRT; inter-rater reliability was 0.88 for FP stories and was 0.96 for control stories. Split-half reliability was 0.78 for FP stories and was 0.85 for control stories. Gender and age comparisons were carried out. Results revealed that women had significantly higher total scores than men in three measures of FPRT.
Keywords: Neuropsychological Testing; Social Cognition; Theory Ofmind; Turkish Tests